PEMBELAJARAN AGAMA ISLAM BAGI ANAK PENYANDANG AUTISME DI SLB YKSB CIJEUNGJING CIAMIS - Aziz, Irfan Miftahul; Rahmanwangsih, Yuli Altri; Darifah, Udung Hari (Jurnal Penelitian Pendidikan Islam, 2016)
This study aims to: 1) find out the learning process of Islamic education in autistic children in YKSB Cijeungjing SLB; 2) knowing the results of learning Islamic education in autistic children in YKSB Cijeungjing SLB; 3) knowing how the school overcome the obstacles in learning. The results of the study are as follows: 1) The process of learning Islamic Education in Autistic Children in YKSB Cijeungjing SLB is carried out in classrooms like schools in general. The strategy used is an individual learning strategy. The method used is lecture method, quantum teaching method, question and answer method, and exemplary method. Media used by computers. 2) Learning Outcomes of Islamic Education in Autistic Children in YKSB Cijeungjing SLB covers cognitive, affective, and psychomotor domains. 3) Constraints in learning include relating to material, behavior, achievement of learning goals, concentration and motivation of students. These obstacles are overcome properly.